Match making for beginners : a novel - Dawson, Maddie (Lake Union Publishing, 2018)
"Marnie MacGraw wants an ordinary life- a husband, kids, and a minivan in the suburbs. Now that she's marrying the man of her dreams, she's sure this is the life she'll get. Then Marnie meets Blix Holliday, her fiancé's irascible matchmaking great-aunt who's dying, and everything changes- just as Blix told her it would. When her marriage ends after two miserable weeks, Marnie is understandably shocked. Marnie doesn't believe she's anything special, but Blix somehow knew she was the perfect person to follow in her matchmaker footsteps. And Blix was also right about some things Marnie must learn the hard way: love is hard to recognize, and the ones who push love away often are the ones who need it most."--book jacket